Parametric description of driving behavior when using automotive Head-Up Displays systems with combiner covering limited areas - Betancur Ramírez, José Alejandro (2018)
In automotive HUD systems there is a strong research trend focused on identifying safety and infotainment interfaces for enhancing the driving experiences. In this way, from the first type of interface, this research focuses on proposing visual HMI identification trends between the driver and a predefined HUD system during a hazard situation; and from the second type of interface, it looks for comparing how different interaction methods for HUD systems focused on haptic, touchless and voice commands could produce different effects on the driver behavior, indicating which of these methods represent for drivers a safety way for interacting with a specific HUD visual interface. Under some specific methodological constrains, the obtained results allow to identify the best way for projecting a visual alert in the HUD system in terms of identification probability and reaction time, and also the best way for interacting with an infotainment interface in terms of driving safety.